Pendayagunaan Iptek dan Pengetahuan Tradisional Untuk Pembangunan Kepemimpinan Kepemudaan dan Kemutakhiran Olah Raga - Dicky Rezady Munaf (Jurnal Sosioteknologi, 2006)
National character development is, among other, determined by Formal-Education process entitled to the citizenries. Beside to improve "leadership-morality", which nowadays requires innovation & technology as a base of human civilization. The aforementioned morale elevation is an answer over quality & competitiveness of next generation's to be a nation, sportivity etc. Tp enable them becoming pioneer in every action & appreciation toward traditional knowledge. In this thesis, such context is detailed for juvanile and sport sectors, also to be explained on recommendation domains of youth & sports developments.